2020
DOI: 10.1016/j.ijrefrig.2020.04.024
|View full text |Cite
|
Sign up to set email alerts
|

General framework for revising class A3 refrigerant charge limits – a discussion

Abstract: D. Colbourne (a) * , K. O. Suen (b) , T-X Li, (c) , I. Vince (d) , A. Vonsild (e) (a) Re-phridge, c/o HEAT GmbH,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The allowable charge quantity for R290 HPs installed in an enclosed space can only reach the upper charge limits if additional measures such as gas detection and ventilation are implemented [25]. However, such safety precautions impose additional challenges that mainly focus on risk assessments regarding 1) the dynamic behavior of refrigerant leakage and dispersion in room enclosures [26] and 2) refrigerant concentration analyses for other types of compartments (including indoor units [27], cabinets [28], car engines, and passenger spaces [29]).…”
Section: Challenges Hindering Wider Application Of Propane Heat Pumpmentioning
confidence: 99%
“…The allowable charge quantity for R290 HPs installed in an enclosed space can only reach the upper charge limits if additional measures such as gas detection and ventilation are implemented [25]. However, such safety precautions impose additional challenges that mainly focus on risk assessments regarding 1) the dynamic behavior of refrigerant leakage and dispersion in room enclosures [26] and 2) refrigerant concentration analyses for other types of compartments (including indoor units [27], cabinets [28], car engines, and passenger spaces [29]).…”
Section: Challenges Hindering Wider Application Of Propane Heat Pumpmentioning
confidence: 99%
“…Recently, Colbourne and Suen 20 have reported that the charge limits could be revised to enable a wider application of A3 refrigerants, with respect to safety regulations and associated implications, concepts and approaches available in published literature. A better method to arrive at charge limits was also proposed.…”
Section: Studies On Refrigerant Leakage From Room Air Conditionersmentioning
confidence: 99%
“…These features limited its use to small refrigeration systems, e.g., air conditioners installed outside buildings, and hermetic commercial equipment and chilled water units. It was assumed that the filling in the chiller would not exceed 150 g of propane in order to ensure the safety of the designed device [30]. In addition, a special electrical equipment was also used to work in an explosive atmosphere.…”
Section: Refrigerant Characteristicsmentioning
confidence: 99%